Tích hợp của các phân bố và toán tử tích hợp - Thành, Đỗ Văn (Journal of Computer Science and Cybernetics, 2016)
The aim of this paper is to show  necessary conditions for aggregation operators such that aggregation processes associated with these operators of distribution are ones of knowledge presentation and treatment. In this paper, according to different aggregation strategies and these conditions, some classes of aggregation operators are proposed.